How Functional and Psychosocial Benefits Impact Customer Value in Internet Shopping using Means-End Chain Approach (Journal of Information Technology and Digital World, 2023)
Marketing and strategic management revolve around customer value analysis and management. However, only some know how cognitive capability affects customer value from a functional and psychosocial perspective. Internet apparel services are transforming retail increasingly after Covid. Thus, marketing managers in the rapidly growing apparel industry must be flexible to predict other customer-valued services. This study examines customer value and functional and psychosocial benefits using cognitive capabilities. Exploratory, confirmatory, and structural equation modelling are used to better understand the relationship between functional and psychosocial benefits and customer value. These complicated benefit combinations promote customer value and help develop value generation and its causes. Using the conceptual model, managers can improve cognitive capabilities by understanding how perceived functional and psychosocial benefits affect value generation for various types of customers.
Keywords: Functional benefits; Psychosocial benefits; Terminal value; Instrumental value; Internet shopping.